Auto Stir Thermos / Mohamad Asyraf Usoff ... [et al.] - Usoff, Mohamad Asyraf; Zikri, Muhammad Amirul Rifqi; Nik Mohd Zailan, Nik Muhammad Aniq Haziq; Khairul Azmi, Khairul Akmal; Faisal, Fikri Zulhafiz (2022)
New Product Development Report is one of the assignments for the Technology Entrepreneurship (ENT600) course. The objective of this assignment is to have a strategy for the development of an innovative product. It is important to introduce the new products to a new market so that the development of the product is known and survived in the industry. Thus, the student needs to gain some data from the market to be analysed and implemented to the new product. It is also important to find unsatisfying needs and potential technology approach solutions to overcome the problem. First and foremost, our product which is thermos (vacuum flask) is classified under improvement and revisions to existing products, whereby it is an innovation to satisfy people’s needs. Research and Development method had been conducted which consists of idea generation, idea screening, market survey, as well as Consumer Trend Canvas (CTC). In this part, a questionnaire for concept testing is distributed to the public to create awareness and obtain several data regarding the product. The survey is carried out for several days and had obtained approximately 10 respondents. In the CTC, basic needs, drivers of change, emerging consumer expectations and inspiration had been analysed. While innovation potential and who are already applied to our innovative product.